Development of an 8051 microcontroller system interfacing trainer - Khee, JunJie. (2009)
The use of a microcontroller trainer would enhance the learning concepts of the 8051 microcontroller that is being taught to students. It would also provide opportunities for students to gain some hands-on experience in building a hardware application that uses the 8051 microcontroller as its main control unit as well as developing a software program using the KEIL Integrated Development Environment for the 8051 microcontroller. This report describes the development of an 8051 microcontroller system interfacing trainer which would be used as an educational tool for microprocessor applications using the Intel 8051 microcontroller architecture. The interfacing trainer would consists of the P89V664 evaluation module, an external circuitry board as well as a simulated heat sensing unit that is currently in its prototyping stage. A monitoring program was developed to enable the 8051 microcontroller to interact with the external circuitry board while the development of the Inter Integrated Circuit (I2C) bus demonstration program illustrates a data transfer application between the microcontroller and the LCD module. Both programs were developed by using the KEIL Integrated Development Environment as well as Flash Magic, a third party application program which facilitates the downloading of the developed programs to the flash memory of the P89V664 evaluation module. An in-depth study of the I2C bus interface was conducted to explore the feasibility of the I2C bus for system designers and equipment manufacturers as well as its functionalities such as its addressing modes, arbitration procedures and the synchronization of the data signals to the clock signals of the I2C bus. It includes a comparison of the I2C bus with the System Management bus as well as a discussion of the application of the I2C bus as a voltage level shifter. Lastly the results from the investigation of the 8051 microcontroller system interfacing trainer as well as the problems that were encountered in the course of investigation would be discussed.